Effect of Ad-hoc Staff Training on Election Outcomes in Kano State, Nigeria - Dutse, Aminu Sani; Ibeme, Nwamaka P.; Ochala, Mark; Zakari, Musa (NIU Journal of Social Sciences; Vol 10 No 3 (2024): NIU Journal of Social Sciences, Vol. 10 No. 3, September 2024DO - 10.58709/niujss.v10i3.2022, 2024)
The study titled “Effect of Ad-hoc Staff Training and Development on Election Outcomes in Kano State, Nigeria”, a quantitative survey research design was adopted. Data collection was done through the administration of structured questionnaires to the population of 300 ad-hoc staff in Kano state. The use of secondary sources includes reports from INEC on its past elections as well as guidelines on the ad-hoc staff training). The data collected were analyzed using inferential and descriptive statistics which include the Analysis of Variance (ANOVA) and multiple regression analysis. The findings of the study have shown that training on technological skills have great impact on the efficiency of Election Day activities, with a p-value of 0.000. On the other hand, the duration of training as an independent variable did not affect the efficiency and accuracy of electoral activities, with a p-value of 0.127. Pre-election training content as an independent variable was found to be statistically significant on the accuracy of electoral outcomes, with a p-value of 0.000. the study concludes that when ad-hoc staffs are well trained, the election delivered are more credible, even with more realistic voter-turnout and vote counts. Consequently, it was recommended that training for ad-hoc staffs should be extensive and effective. INEC should ensure training on technological expertise as well as the pre-election training on the conduct and ethics of electoral processes. Also, periodic training should be carried out as part of the refresher courses aimed at ensuring staff competence and updates on innovations in the electoral process. Keyword: Ad-hoc Staff Training, Election Outcomes, election technological skills and duration of training